Violation of the Principle of Cooperation in Bertolt Brecht's Drama Der Gute Mensch von Sezuan - Eka Fitriyana; Iman Santoso (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2025)
This study aims to describe (1) the types of violations of the principle of cooperation and (2) the implicature in Bertolt Brecht's play Der Gute Mensch von Sezuan. The data collection methods and techniques used were the “Simak Bebas Libat Cakap” method and reading and note-taking techniques. Data analysis was carried out using the referential matching method and the basic technique of “Pilah Unsur Penentu”. The results of this study indicate that: 1) there were 35 instances of violations of the principle of cooperation, namely violations of the maxim of quantity (13 instances), violations of the maxim of quality (5 instances), violations of the maxim of relevance (10 instances), and violations of the maxim of performance (7 instances). The most frequent violation was a violation of the maxim of quantity; 2) there were 17 types of implicatures in violations of the principle of cooperation, namely a) showing respect, b) sarcasm, c) expressing doubt, d) mockery, e) expressing dislike, f) providing information, g) evoking pity, h) showing anger, i) convincing, j) concealing something, k) rejecting something, l) showing concern, m) changing the topic of conversation, n) asking for advice, o) accepting a request, p) boasting, q) seeking information. The implicature of concealing something is the most commonly found implicature. This is because the main plot of this play is disguise.